Christian concepts in the works by the Ukrainian poet Viktor Boiko - Chernenko, Olha; Malenko, Olena; Holoborodko, Kostiantyn; Bozhko, Yuliia; Shaposhnikova, Olena Leonidivna (My University, 2024)
The article aims to analyse the quantitative and qualitative aspects of the implementation of elements of Christian concepts “God” and “Soul” in the language of poetry by Viktor Boiko – Ukrainian artist of the late twentieth – early twenty-first century. A comprehensive qualitative analysis is employed to study the peculiarities of verbalization of numerous semantic planes of the mentioned concepts in the works by Viktor Boiko. It has been found that in the Ukrainian language space elements of th Christian conceptsphere are realised in biblical, folklore and linguistic interpretation, in semiotic and verbal planes, in synchronic and diachronic aspects and are accordingly reflected in the language of Ukrainian writers. It has been concluded that the elements of the concepts of “God” and “Soul” are a part of the linguistic picture of the world of any ethnic group, which manifests the language of poets who show their attitude to a higher power as a protector and interlocutor. That is why Viktor Boiko, as a Ukrainian poet, syncretically combining patriotism and lyrics, politics and everyday motives, satire and good humour in his works, looking for certain trends in the universe, turns to Christian concepts within the framework of “quiet poetry”.

Мета статті- проаналізувати кількісний і якісний аспекти реалізації елементів християнських концептів «Бог» і «Душа» в мові поезії Віктора Бойка – українського митця кінця ХХ – початку ХХІ ст. Комплексний якісний аналіз застосовано для вивчення особливостей вербалізації численних семантичних площин згаданих концептів у творах Віктора Бойка. З’ясовано, що в українському мовному просторі елементи християнської концептосфери мають реалізацію в біблійній, фольклорній і власне лінгвістичній інтерпретації, у семіотичній та вербальній площинах, у синхронічному й діахронічному аспектах і відповідно відображені в мовотворчості українських літераторів. Установлено, що елементи концептів «Бог» і «Душа» входять до мовної картини світу будь-якого етносу, з чим маніфестують мовотворчість поетів, які виявляють своє ставлення до вищої сили як захисника і співбесідника. Тому й Віктор Бойко як український поет, синкретично сполучаючи у своїх творах патріотизм і лірику, політику й побутові мотиви, сатиру й добрий гумор, шукаючи певних тенденцій світобудови, звертається до християнських концептів у межах «тихої поезії».
Християнські концепти у творчості українського поета Віктора Бойка
Keywords: concept "God"; concept "Soul"; Viktor Boiko; poetry; linguistic picture of the world; концепт "Бог"; концепт "Душа"; Віктор Бойко; поезія; мовна картина світу